Pemberian Kompensasi, Motivasi dan Kepemimpinan terhadap Kinerja - Sri Mulyati (JURNAL PUNDI, 2020)
The high level of irregularities that occur in government agencies both in the form of deviations of power, responsibility and trust has shown how low performance, especially in complying with work regulations and prevailing social norms in carrying out the tasks assigned. The purpose of this study was to analyze the effect partially and simultaneously on compensation, leadership and motivation on performance. The populations in this study were all nurses working in the hospital in Tasikmalaya based on employment data of 199 people. Proportional sampling techniques are as many as 67 people. The results showed that partially compensation had a significant effect on Nurse's performance. Partially leadership had a significant effect on Nurse's performance. Partially motivation had a significant effect on Nurse's performance. Simultaneous compensation, leadership and motivation had a significant effect on Nurse's performance.Keywords: Compensation, Leadership, Motivation, Performance